P069 LOW FAT DIET IMPROVES QUALITY OF LIFE AND CHANGES THE MICROBIOME IN A CATERED, CROSS-OVER DESIGN INTERVENTION OF UC PATIENTS WITH QUIESCENT DISEASE: RESULTS OF A PILOT STUDY. (18th January 2018) - Phillips, Matthew C; Quintero, Maria Alejandra; Martinez, Adriana; Kerman, David; Deshpande, Amar R; Damas, Oriana; Pignac-Kobinger, Judith; Santaolalla, Rebeca; Knight, Karina; Rodriguez, Vanessa; Abreu, Maria
Abstract: A diet high in animal meat and fat has been linked to an increased risk for ulcerative colitis (UC) and high meat intake increases the likelihood of UC flares. Despite these correlations, there has never been a controlled, prospective study to investigate the contribution of dietary fat to inflammation and the quality of life in patients with UC. In this pilot, cross-over design study, patients with UC were randomized and given two, 4 week, isocaloric dietary interventions with a 2 week wash out between diets: a low fat diet (LFD), containing 10% total calories from fat, and a standard American diet (SAD), containing 35–40% total calories from fat. Patients were provided daily, catered food to ensure standardization of the diets. Patients had to be in remission or only mildly active and have had a flare within the past 18 months. To assess improvement in quality of life (QoL), patients completed the Inflammatory Bowel Disease Questionnaire (IBDQ) before and after each diet. Biochemical markers of inflammation were measured in the stool and serum and stool was collected for microbiome analysis. Eight patients completed both dietary interventions. Patients experienced a significant increase (p=0.01) in their QoL, as measured by the IBDQ, while on the LFD as compared to the SAD. Results were consistent regardless of the initial diet. Patients on LFD had significant changes in the composition of their microbiome including a significant increase in the relative abundance of Bacteroidetes (p>0.05). Changes in the microbiome also correlated with patient's IBDQ and with serum levels of CRP, IL-6, and IL-1b. Our data indicate that a LFD improves the QoL of patients with quiescent or mild UC and this improvement is correlated with changes in the microbiome. The LFD also increased the abundance of bacteria traditionally associated with a healthy microbiome. This simple dietary intervention would provide clinicians an informed recommendations to improve the QoL their patients.